2022
DOI: 10.5296/ijele.v10i2.20439
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by EFL Teachers and Learners in Providing and Receiving Online Corrective Feedback on Writing Assignments

Abstract: The COVID-19 pandemic has negatively impacted most sectors on a global scale. In most places around the world, education has transitioned to a fully online mode. During the pandemic, online learning was the most appropriate alternative for continuing education, particularly at the tertiary level, though this transition was not without inherited challenges. A mixed-methods study investigated English as a Foreign Language (EFL) teachers’ and students’ attitudes towards and beliefs surrounding the use of online c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This finding is relevant to Salameh & Hawarna (2023) who found that insufficient digital technology proficiency and difficulty is one of the challenges that face EFL teachers. This finding is also as the same as in the study of Alsahli and Meccawy (2022), Mariadi Mariadi (2022) and Dicky Meiantoni and others (2021).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is relevant to Salameh & Hawarna (2023) who found that insufficient digital technology proficiency and difficulty is one of the challenges that face EFL teachers. This finding is also as the same as in the study of Alsahli and Meccawy (2022), Mariadi Mariadi (2022) and Dicky Meiantoni and others (2021).…”
Section: Discussionsupporting
confidence: 91%
“…There are many studies that their findings reveal that challenge encountered by EFL teachers have related to internet cost and connection. For instance, the study of Salameh & Hawarna (2023), Dewi and others (2023), Alsahli and Meccawy (2022), Mariadi Mariadi (2022), Yulianto and Mujtahin (2021), Dicky Meiantoni ,et al (2021), Zboun & Farrah (2021) and Arif (2020) are all have the same results.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation